A New Way to Silicone‐Based Peptide Polymers1. Issue 12 (4th February 2015) - Jebors, Said; Ciccione, Jeremie; Al‐Halifa, Soultan; Nottelet, Benjamin; Enjalbal, Christine; M'Kadmi, Céline; Amblard, Muriel; Mehdi, Ahmad; Martinez, Jean; Subra, Gilles
Abstract We describe a new class of silicone‐containing peptide polymers obtained by a straightforward polymerization in water using tailored chlorodimethylsilyl peptide blocks as monomeric units. This general strategy is applicable to any type of peptide sequences, yielding linear or branched polymer chains composed of well‐defined peptide sequences.